Selected aspects of energy efficiency improvement of heat supply to buildings according to WT2021 standards - Koczergo, Katarzyna; Niemyjski, Olgierd (Instal, 2020)
The promotion of energy-efficient construction in the European Union countries started as early as in 2002, when new rules and guidelines for designing and modernizing buildings were introduced to reduce energy consumption for central heating, hot water and ventilation purposes. In the following years, new standards for energy-efficient construction were defined as well as rules and regulations for improving the energy efficiency of heat production and distribution to end users. The article presents selected issues concerning the possibility of meeting the requirements specified in the Technical Conditions for 2021. Providing these energy standards is strongly dependent on the type of heat source used for the building. This dependence is presented on the example of the building in which several variants of the heat source were adopted. Additionally, the directions of modernization of heating networks were presented in order to reduce heat losses, which also improves energy efficiency of heat distribution through the heating network.